The Portrayal of Class Struggle in Victoria Aveyardâ€™s Novel â€œRed Queenâ€ - Muh. Izha Ashari; Rasiah Rasiah (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2020)
This study is aimed to describe the social condition and distinction in Victoria Aveyardâ€™s novel Red Queen. The research question of the study is â€œHow is class struggle represented symbolically in Red Queen by Victoria Aveyard?â€. There are two sources of data in this study, they are the Red Queen novel by Victoria Aveyard as primary data and supported by other studies as secondary data. The data is collected through reading and understanding carefully the novel, identifying the symbols which referred to social class representation in the novel, identifying the data, and grouping it in a catalog based on specific headings. The technique of data analysis is done through presenting the data, describing the data, interpreting the data, and concluding the data. The findings of this study showed that the Red Queen novel portrayed two social classes in society. Red symbolizes the Rednecks in the United States as the working-class or proletariat and Silver symbolizes the bourgeoisie or rich capitalist people. This social distinction then creates a class struggle that leads the working-class to free from the exploitation of capitalists.